Use of novel non‐invasive techniques and biomarkers to guide outpatient management of fluid overload and reduce hospital readmission: systematic review and meta‐analysis. (22nd July 2021) - Zisis, Georgios; Halabi, Amera; Huynh, Quan; Neil, Christopher; Carrington, Melinda; Marwick, Thomas H.
Abstract: Aims: Fluid congestion is a leading cause of hospital admission, readmission, and mortality in heart failure (HF). We performed a systematic review and meta‐analysis to determine the effectiveness of an advanced fluid management programme (AFMP). The AFMP was defined as an intervention providing tailored diuretic therapy guided by intravascular volume assessment, in hospitalized patients or after discharge. The AFMP group was compared with patients who received standard care treatment. The aim of this systematic review and meta‐analysis was to determine the effectiveness of an AFMP in improving patient outcomes. Methods and results: A systematic review of randomized controlled trials, case–control studies, and crossover studies using the terms 'heart failure', 'fluid management', and 'readmission' was conducted in PubMed, CINAHL, and Scopus up until November 2020. Studies reporting the association of an AFMP on readmission and/or mortality were included in our meta‐analyses. Risk of bias was assessed in non‐randomized studies using the Newcastle–Ottawa Scale. From 232 retrieved studies, 12 were included in the data synthesis. The 6040 patients in the included studies had a mean age of 72 ± 4 years and mean left ventricular ejection fraction of 39 ± 8%, there were slightly more men ( n = 3022) than women, and the follow‐up period was a mean of 4.8 ± 3.1 months. Readmission data were available in 5362 patients; of these, 1629 were readmitted. Mortality data were available in 5787 patients; of these, 584 died. HF patients who had an AFMP in hospital and/or after discharge had lower odds of all‐cause readmission (odds ratio—OR 0.64 [95% confidence interval—CI 0.44, 0.92], P = 0.02) with moderate heterogeneity ( I 2 = 46.5) and lower odds of all‐cause mortality (OR 0.82 [95% CI 0.69, 0.98], P = 0.03) with low heterogeneity ( I 2 = 0). The use of an AFMP was equally effective in reducing readmission and mortality regardless of age and follow‐up duration. Effective pre‐discharge diuresis was associated with significantly lower readmission odds (OR 0.43 [95% CI 0.26, 0.71], P = 0.001) compared with a fluid management plan as part of post‐discharge follow‐up. Conclusions: An effective AFMP is associated with improving readmission and mortality in HF. Our results encourage attainment of optimal volume status at discharge and prescription of optimal diuretic dose. Ongoing support to maintain euvolaemia and effective collaboration between healthcare teams, along with effective patient education and engagement, may help to reduce adverse outcomes in HF patients.